The royal nanny - Carlson, Melody (WhiteCrown Publishing, 2026)
"Former teacher Meredith Cardwell thought everything was going to plan...until suddenly it wasn't. Strapped and stranded alone in Austria on what was supposed to be a romantic trip for two, Meredith signs on for a short-term nannying gig. Unbeknownst to her, it's for royalty. But with no money and no other options to get home, Meredith takes a leap of faith that children are children...regardless of where they grow up. In over her head from day one, Meredith does her best to connect to and help the two children, but the transition from childcare in the jungle of the South Pacific to a royal household is anything but straightforward. Yearning for a mother-figure, the young prince of Rotslavia clings to Meredith, while his tween sister acts with the bossiness of her future role as queen. All the while, questions abound. Where is their father? Why does he seem to neglect them? And what will she do when they return to their homeland? Of course, she gets to know the prince, and to love his children, but an everyday American girl can never really fit into the royal world...can she?"--P. [4] of cover.